Person-centered healthcare in the information age: Experiences from a user driven healthcare network - Price, A; Biswas, T; Biswas, R (University of Buckingham Press, 2014)
Person-centered healthcare is central to the practice of compassionate medicine. The practice of person-centered healthcare occurs when intuitive and organizational thinking is engaged harmoniously, rather than in competition. Present healthcare systems relegates core providers and patients to 10-minute appointments for the purpose of meeting budgetary or patient access targets. It is unrealistic to expect such a system to be sufficient to share values and expertise. Often, important questions are left to those without the experience or expertise to answer. Person-centered healthcare can empower people to escape from fragmented medical care and displaced knowledge. The roles of patient and doctor can better serve medicine by asking all to go beyond their assigned roles to communicate and form relationships. These working partnerships will respect individual and role-based values, strengths and weaknesses. Being a patient is a condition or state somewhere between death and life that it is common to all. The patient is not an entity, but a person. Providing medical care is a profession, it is what physicians do, not who they are. Without cooperation between doctor and patient, medical intervention loses power and effectiveness. The consultation may be temporarily seized by social force and dominance, but it is maintained by respect and relationship. Respect is earned and negotiated by listening, observing and then acting in the best interests of others. This requires sensitive negotiation and the desire to build the bridges in medicine between knowledge and need. Great negotiators make it their business to know the strengths, values, needs and limitations of others. Power is intrinsically bound to what we value. What we value is what we will invest in. Let us assess the conditions we have to work with, reason together and build respect, access and relationships in healthcare.